Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T11:31:36+01:00
Wykonaj działania:
6(x-4)-2=6x-24-2=6x-26
2(x+1)-3(x-1)=2x+2-3x+3=-x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(y+2)=5x-5y-5-4y-8=5x-9y-13
2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
½(4x-4)-2x=2x-2-2x=-2
x(x-1)-3(x²-x)=x2-x-3x2+3x=-2x2-2x
5a(a-3)-3a(a-5)=5a2-15a-3a2+15a=2a2
3x(?????+⅓y)-2y(½x-½)=w tym przykładzie brak liczby
2010-03-10T11:35:45+01:00
6(x-4)-2 = 6x - 26

2(x+1)-3(x-1) = 5 - x

-3(y-2)+4(y+2) = y + 14

5(x-y-1)-4(y+2) = 5x - 9y - 13

2(3a+b)-2(a-b) = 4a + 4b

½(4x-4)-2x = -2

x(x-1)-3(x²-x) = 2x - 2x²

5a(a-3)-3a(a-5) = 2a²

3x(+⅓y)-2y(½x-½) = ? czegoś brakło na początku ;p